Bibliometric Analysis of Strategic Management and Meaningful Work: Trends, Collaboration, and Future Directions - Sunardjo, Richard Andre; Riza Chakim, Mochamad Heru; Natalia, Ester Ananda; Rahardja, Untung; Sihotang, Sondang Visiana (International Journal of Engineering, Science and Information Technology, 2025)
This study explores the evolution of Strategic Management and Meaningful Work (SDG-8) research through a bibliometric analysis of Scopus-indexed publications from 2015 to 2025. The aim is to map global trends, collaboration networks, and thematic clusters, thus enhancing understanding of how strategic management practices align with team member well-being and sustainable business models. Building on established literature in sustainable business, digital transformation, and ethical leadership, the research integrates human resource management and organisational behaviour theories. It examines how strategic management interacts with meaningful work, drawing on previous bibliometric and conceptual studies. A keyword-based search in the Scopus database identified 222 publications, refined to 110 English-language articles, conference papers, and reviews. VOSviewer software was used to construct co-occurrence networks and thematic maps across countries, organisations, authors, and keywords. The analysis reveals a significant increase in research output, with key hubs in the United States, Switzerland, Australia, and China. Influential institutions include MIT, Harvard T.H. Chan School of Public Health, and Wageningen University. Emerging themes such as digital transformation and competitive advantage underscore the growing integration of strategic management with meaningful work. These findings highlight the necessity for enhanced international collaboration to advance sustainable business practices and promote team member well-being.